Translation Method Of Phrasal Verb In Novel Eat Pray Love By Elizabeth Gilbert - Krisna Adi Candra, I Made (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2016)
The aim of this research is to investigate the translation of  phrasal verb by applying the translation theory proposed by Newmark. The data were taken from a novel entitled Eat Pray Love and its translation entitled Makan Doa Cinta written by Elizabeth Gilbert. The data in this research are phrasal verbs in Source Language and its translation in Target Language which is Bahasa Indonesia . The data in this article were collected using documentation method followed by note taking. Then, the data were analyzed descriptively using the exponential mapping adopted from Natural Semantic Metalanguage theory and 64 semantic primes proposed by Wierzbicka. The result shows that the method of translation used by the translator was the communicative translation method with a percentage of 98, 33%, and 1, 66% was left untranslated. This supports that no phrasal verb in Source Language translated into phrasal verb in target language; moreover, the aesthetic and emotional elements of Source Language were omitted. Based on the analysis done by using Natural Semantic Metalanguage theory, out of 60 phrasal verbs in Source Language, 59   were translated into Target Language and one was omitted.
Keywords: phrasal verb, method of translation, natural semantic metalanguage